Interaction of anthocyanins with drug-metabolizing and antioxidant enzymes - Bártíková, H; Skálová, L; Dršata, J; Boušová, I (Current medicinal chemistry, 2013)
Anthocyanins are generally considered to be the largest and the most important group of water-soluble pigments in plants. They are widely consumed by humans as natural compounds of vegetables, fruits, and red wine. Anthocyanins as well as other flavonoids show protective qualities against variety of pathologies, including cardiovascular diseases, cancer, diabetes mellitus, neurodegeneration, inflammation, viral infections, and obesity. Many healthy properties of anthocyanins are related to their antioxidant potency. Broad evidence of beneficial effects of anthocyanins on human health has led to their increasing popularity in the form of food supplements and nutraceuticals. As the nutraceuticals contain concentrated bioactive agents, consumed doses exceed those that could be obtained from food. Therefore, apart from anticipated improvement of human health it is essential to have in mind possible unexpected effects of anthocyanins. Interaction of these compounds with drug-metabolizing enzymes and transporters may affect the fate of co-administered drugs and thus exert pharmacological consequences. On the other hand, the modulation of certain drug-metabolizing and antioxidant enzymes by anthocyanins can contribute to chemoprotection and antioxidant defense of organisms. The present review summarizes anthocyanin properties with emphasis on the antioxidant capacity and deals with the potential of anthocyanins to modulate phase I and II drug-metabolizing enzymes, transporters and antioxidant enzymes. The undesirable and/or beneficial outcomes of possible interactions of anthocyanins with drugs or industrial pollutants are also discussed.
Keywords: oxidoreduktasy; léčivé přípravky; nádory; Pharmaceutical Preparations; systém (enzymů) cytochromů P-450; Animals; Anthocyanins; lidé; Neoplasms; lékové interakce; Drug Interactions; Cytochrome P-450 Enzyme System; Humans; zvířata; anthokyaniny; Oxidoreductases